The role of Good Faith in South African Contract Law: a critical analysis of the Beadica Judgement - Maesela, Nandi (Department of Commercial Law, 2022)
South African courts and academics alike have grappled with ascertaining the exact role that good faith plays in the law of contract for years now. Determining the proper operation and application of this principle has lent itself to many problems that have manifested in an inconsistent application of the principle of good faith and, therefore, a lack of predictability and certainty in how cases involving good faith will be decided by our courts. At the heart of the issue lies the tension between the competing goals of freedom of contract/certainty on the one hand and fairness on the other. As a result, the question of when a court may intervene in contractual dealings between parties and refuse to enforce an otherwise valid contractual term that has been freely and voluntarily entered into has been the subject of much debate. After years of having the principle of good faith inconsistently applied by our courts and witnessing a noticeably incongruent approach taken by the Supreme Court of Appeal and the Constitutional Court on the matter, this very question received much needed attention in a recent judgment by our Constitutional Court in the case of Beadica 231 CC & Others v Trustees for the time being of the Oregon Trust & Others. Following this latest judgment by our Constitutional Court on the matter, the pertinent question now is whether the uncertainty surrounding the proper application of the role of good faith in contract law has been satisfactorily addressed and the matter sufficiently settled. This thesis aims to answer this exact question by engaging in a critical analysis of the Beadica judgment. In analysing the judgment the aim is to answer namely two questions, the first is whether the matter has in fact been definitively settled by our court in this recent judgment and if so, what the current role of good faith can be understood to be in our law of contract today. The second question is whether, in arriving at the precedent set in Beadica, the court has adequately fulfilled its mandate to develop the law of contract in accordance with Constitutional values and uphold the principle of ‘transformative constitutionalism' and if not, whether further development of the principle is still needed, either by developing our common law through our courts or creating further legislation on the matter.